Domain Pinning: Comparison of Hafnia and PZT Based Ferroelectrics. (8th March 2017) - Fengler, Franz P. G.; Pešić, Milan; Starschich, Sergej; Schneller, Theodor; Künneth, Christopher; Böttger, Ulrich; Mulaosmanovic, Halid; Schenk, Tony; Park, Min Hyuk; Nigon, Robin; Muralt, Paul; Mikolajick, Thomas; et al.
Abstract : Even though many studies on the field cycling behavior of ferroelectric hafnium oxide have recently been published, the issue is still not fully understood. The initial increase of polarization during first cycles is explained by different theoretical and empirical approaches. Field‐induced phase changes as well as oxygen vacancy diffusion from interfacial layers toward the bulk are discussed. Trapped charges as well as the mentioned oxygen vacancy diffusion might cause a shift of the hysteresis along the voltage axis called imprint. Even though various studies connect this effect to charge diffusion with progression of cycling, a final experimental proof for the origin of wake‐up and imprint is still missing. Based on the comprehensive comparative study of hafnia–zirconia and iron‐doped lead zirconate titanate ferroelectrics, it is verified that the diffusion of oxygen vacancies is the main cause for both imprint and wake‐up. Moreover, it is shown that a local seed inhibition of ferroelectric domains is most likely responsible for the reduced ferroelectric response in pristine state. Abstract : Based on comparative study of hafnia–zirconia and lead zirconate titanate, the diffusion of oxygen vacancies is verified as the cause for wake‐up and imprint phenomena. Similar effects are visible in both materials, resulting in a local seed inhibition of ferroelectric domains that are responsible for a reduced ferroelectric response in the pristine state.